Short-Circuit Calculation in Unbalanced Three-Phase Power Distribution Systems with Distributed Generation - Reiz, Cleberton [UNESP]; Leite, Jônatas Boás [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This work proposes a method to calculate the short- circuit currents in unbalanced three-phase power distribution systems with distributed generation (DG) from non- and renewable energy resources. It takes into account the physical and operational features of four different types of DGs: synchronous, induction, photovoltaic and double-fed induction generator (DFIG). The DG formulations depend upon the connection type that can be directly coupling to the power grid or by using electronic converters or coupling transformers. The proposed method uses the bus impedance matrix with Kron reduction for each generator and superposition conception in the short-circuit current calculation. The results are achieved under a real-work unbalanced distribution network with 135 buses providing typical values of the short-circuit current that are compared with values from commercial software in the evaluation of the proposed methodology.
Keywords: Bus Impedance Matrix; Distributed Generation; Electrical Power Distribution System; Kron Reduction; Non- and Renewable Energy Resource; Short-Circuit